On discontinuing dialysis - Wight, J. (Journal of medical ethics, 1993)
Ethical issues relating to the withdrawal of dialysis are discussed, comparing dialysis with other life-support systems, particularly artificial ventilation. It is argued that there is no ethical difference between discontinuing treatment in each case. One practical difference between the two is that patients with chronic renal failure are less likely to have reduced autonomy, and so can engage in discussions with their doctors regarding the situations in which their life-supporting treatment might be discontinued. It is argued that doctors caring for patients on dialysis have an ethical duty to discuss with these patients the circumstances in which they may wish to discontinue dialysis.